Femoral Anteversion In Relation ToMuscle Strength And Selective Motor Control In Children With Spastic Diplegia - Shimaa Khaled Hamed; e; Walaa Abd ElHakiem Abd El-Nabie; Amira Farag Hamed (2025)
Background: Children with cerebral palsy suffer from deficits in muscle strength, motor control, and have increase in femoral anteversion angle.Purpose: The purpose of this study was to investigate the correlation of femoral anteversion, muscle strength and selective motor control in children with spastic diplegic cerebral palsy. Methods: Seventy-two children with spastic diplegia aged fromsix to eight years participated in this study, their femoral anteversion angle ranged from 20 to 50 degree which was assessed by craig$1 (Bs test, while muscle strength (hip abductor and extensor) and selective voluntary motor control were evaluated using laffayte manual muscle tester, and Selective Control Assessment of the Lower Extremity scalerespectively. Results: There was non significant negative correlation of femoral anteversion with muscle strength of hip abductors andextensors (r = -0.120,r = -0.053 respectively).In addition, there was significant negative correlation of femoral anteversion with the overall selective motor controlscore and ankledorsiflexion/planterflexion. Conclusion: Increased femoral anteversion may lead to poor selective motor control in children with diplegic cerebral palsy, but it has no effect on muscle strength of hip abductor or extensor.s
(3GdNdajI(B: (3GdCWaGd GdeUGHhf HGdTdd GdOeGZj jYGfhf ef YLR aj bhI GdYVdGJ hGdJMce GdMQcj hRjGOI RGhjI GdGdJhGA GdGeGei ddaNP(B.(3GdgOa(B: (3cGfGdgOa ef gPg GdOQGSI gh GdJMbjb aj GdYdGbI HjfRGhjI GdGdJhGA GdGeGei ddaNP hbhI GdYVdGJ hGdJMce GdGfJbGFj aj GdMQcI dOi GdCWaGd GdeUGHjfHGdTdd GdOeGZj GdJbdUj GdeROhL(B. (3GdWQjbI(B: (3TGQc aj gPg GdOQGSI GKfGf hSHYhf WadkG eUGHjf HGdTdd GdOeGZjGdJbdUj GdeROhL JQGhMJ CYeGQge Hjf SJ Edi KeGfj SfhGJ(B. (3JQGhMJ RGhjI GdGdJhGA GdGeGeiddaNPddGWaGd GdeTGQcjf ai GdOQGSI ef (B20 (3Gdj (B50 (3OQLI hJe JbjegG HGSJNOGe GNJHGQ cQjL HjfeG Je Jbbje bhI GdYVdGJ (B((3GdeHYOI hGdHGSWI ddaNP(B) (3hGdJMce GdGfJbGFj aj GdMQcI HGSJNOGe LgGR dGajJ dbjGS bhI GdYVdGJ hebjGS Jbjje GdJMce GdGfJbGFj ddCWQGa GdSadjI Ydi GdJhGdj(B. (3GdfJGFL(B:(3GXgQJ GdfJGFL hLhO GQJHGW SdHi ZjQ eDKQ GMUGFjG Hjf RGhjI GdGdJhGA GdGeGei ddaNP hbhI GdYVdGJ(B)(3GdeHYOI Ch GdHGSWI(B(.(3ceG cTaJ GdOQGSI Yf hLhO GQJHGW SdHj Ph OdGdI GMUGFjI HjfRGhjI GdGdJhGA GdGeGei ddaNP h GdJMce GdMQcj GdGfJbGFjHTcd YGe heaUd GdcGMd HTcd NGU(B. (3GdGSJfJGL(B: (3RjGOI GdGdJhGA GdGeGeiddaNPbO JDOi Gdj VYa GdJMce GdMQcj GdGfJbGFj dOi GdCWaGd GdeUGHjf HGdTdd GdOeGZjGdJbdUj GdeROhLhdG JDKQ Ydi bhI GdYVdGJ(B)(3GdeHYOI Ch GdHGSWI ddaNP(B(.s
Thesis (M.Sc)-Cairo University, 2025.
Bibliography: pages 70-83.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Physical therapy; (3GdYdGL GdWHjYj s; Cerebral palsy -- Diplegia -- Femoral anteversion -- Muscle strength -- Selective motor control